A MUSE study of NGC 7469: Spatially resolved star-formation and AGN-driven outflows. Issue Volume 15:Issue S359(2020) (March 2019) - Robleto-Orús, A. C.; Torres-Papaqui, J. P.; Longinotti, A. L.; Ortega-Minakata, R. A.; Sánchez, S. F.; Ascasibar, Y.; Bellocchi, E.; Galbany, L.; Chow-Martínez, M.; Trejo-Alonso, J. J.; Morales-Vargas, A.; Romero-Cruz, F. J.; et al.
Abstract: NGC 7469 is a well-known type 1 AGN with a cirumnuclear star formation ring. It has previous detections of X-rays warm absorbers and an infrared biconical outflow. We analysed archival MUSE/VLT observations of this galaxy in order to look for an optical counterpart of these outflows. We report spatially resolved winds in the [O III] λ5007 emission line in two regimes: a high velocity regime possibly associated with the AGN and a slower one associated with the massive star formation of the ring. This slower regime is also detected with H β .